THE EFFECT OF PROJECT BASED LEARNING MODEL WITH WAMENA LOCAL WISDOM ON LEARNING OUTCOMES AND PROBLEM SOLVING OF GRADE V ELEMENTARY SCHOOL STUDENTS IN WAMENA - Yuliana Eva; I Made Citra Wibawa; I Gede Margunayasa (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the effects of Project-Based Learning (PjBL) integrated with Wamena local wisdom on elementary students’ learning outcomes and problem-solving skills. Integrating culturally relevant pedagogy into innovative learning models is expected to enhance meaningful learning, particularly in remote regions with strong local traditions. A quasi-experimental design employing a non-equivalent pretest–posttest control group was used. The participants were 112 fifth-grade students from two elementary schools in Wamena, Indonesia. Data were collected using learning outcome tests and problem-solving assessments and analyzed using multivariate analysis of variance (MANOVA). The results indicate significant differences in learning outcomes and problem-solving skills between students taught using PjBL integrated with local wisdom and those taught using conventional learning models. Students in the PjBL group achieved higher scores in both dependent variables. These findings demonstrate that integrating local wisdom into project-based learning enhances students’ conceptual understanding and problem-solving abilities. This study contributes to elementary education literature by highlighting the pedagogical value of culturally contextualized project-based learning in improving learning quality in geographically and culturally distinctive regions.